2005
DOI: 10.1258/rsmvasc.13.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Civil and War Peripheral Arterial Trauma: Review of Risk Factors Associated with Limb Loss

Abstract: We sought to analyze the early results of civil and war peripheral arterial injury treatment and to identify risk factors associated with limb loss. Between 1992 and 2001, data collected retrospectively and prospectively on 413 patients with 448 peripheral arterial injuries were analyzed. Of these, there were 140 patients with war injuries and 273 patients with civil injuries. The mechanism of injury was gunshot in 40%, blunt injury in 24%, explosive trauma in 20.3%, and stabbing in 15.7% of the cases. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
(35 reference statements)
2
22
1
4
Order By: Relevance
“…Blunt traumas and gunshot wounds are more likely to affect the arterial supply at more than 1 level. More extensive injury to the vessel and surrounding structures leads to severe interruption of the main as well as collateral blood supply, complicating the management of these injuries and likely explaining the higher amputation rates compared with stab wounds 4,5,9. Consistent with previous reports, we found that stab trauma in particular is associated with a 10-fold decreased risk of multilevel arterial injury, bone fractures, and tissue destruction compared with other injury patterns.…”
Section: Discussionsupporting
confidence: 88%
“…Blunt traumas and gunshot wounds are more likely to affect the arterial supply at more than 1 level. More extensive injury to the vessel and surrounding structures leads to severe interruption of the main as well as collateral blood supply, complicating the management of these injuries and likely explaining the higher amputation rates compared with stab wounds 4,5,9. Consistent with previous reports, we found that stab trauma in particular is associated with a 10-fold decreased risk of multilevel arterial injury, bone fractures, and tissue destruction compared with other injury patterns.…”
Section: Discussionsupporting
confidence: 88%
“…War-related arterial injuries are a challenge to manage and may result in different ways, from simple injuries caused by low energy basic devices to complex injuries caused by high energy explosive and destructive devices. [1][2][3]9,10] We are now regularly encountering these kinds of injuries due to the Syrian Civil War in parallel to the literature. The hospital where the injured people are treated is located in Hatay, near the border with Syria in southernmost Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…An effective modification of that technique is to apply two tourniquets, one high on the limb and the second 8 cm above the wound. Then the first one is released, while the second stays closed [3,7].…”
Section: Prehospital Care In Patients With Vascular Injury 21 On-sitmentioning
confidence: 99%